The repercussions of the Hungarian revolutionary movement 1848-1849 - Khadir, Ass. Prof. Dr. Narjis Karim (Thi Qar Arts Journal, 2024)
The Hungarian Revolution of 1848-1849 is one of the most wonderful revolutions that the European continent has witnessed, which was influenced by the winds of the February Revolution of 1848 in France. The French February Revolution sparked revolutions throughout Europe against the absolute rule of the Habsburgs, Bourbons. During it, the Hungarians recorded the most wonderful images of heroism in confronting the imperial tyranny of the Habsburg government, in order to get rid of the injustice, oppression and inequality that the Hungarians were suffering from. The revolution included large parts of the country with the aim of bringing about a complete change in the political, social and economic system. The media, represented by newspapers and magazines, played an important role in keeping the people informed of political developments. Hungarian poets such as Sandor Petofi and János Aranyi supported the reform movement and contributed significantly to it. The liberal Hungarian leaders, along with their forces, were able to achieve the desired victories at the beginning of the revolution and force Emperor Ferdinand to declare a constitution for the country that guaranteed its independence and the civil rights of its people, the imposition of taxes under the control of parliament, and the freedom of association. However, things later got out of control, especially after Emperor Joseph, who succeeded his uncle, sought help from the Russian forces, which declared their readiness, as the leader of the Holy Alliance that rejected and opposed all revolutionary action. The end of the matter was the end of the revolution and its suppression in Hungary, and the Austrian forces were able to tighten their grip on the country and return it to its previous situation, if not worse.